1996
DOI: 10.1002/ana.410400213
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous neurological recovery after stroke and the fate of the ischemic penumbra

Abstract: We prospectively tested the hypothesis that early recovery after ischemic stroke depends on the ultimate survival of functionally impaired, critically ischemic (i.e., "penumbral") tissue. From a series of 26 consecutive patients studied with positron emission tomography within 18 hours of first-ever stroke in the middle cerebral artery territory, all 11 survivors to the 2-month end point who exhibited increased oxygen extraction fraction were declared eligible. The positron emission tomographic images were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
293
3
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 469 publications
(324 citation statements)
references
References 38 publications
(50 reference statements)
23
293
3
5
Order By: Relevance
“…These apparent discrepancies might reflect species differences but also the small degree of neuronal death in S1, the lack of co-registration between fMRI and histopathology, and the fact that fMRI was performed under general anesthesia, in the Sicard study. 42 Behavioral Correlates Although avoiding infarction of the penumbra markedly benefits behavioral outcome, 86,87 whether SNL may limit or delay functional recovery and plastic processes in the immediate periinfarct tissue, known to partly underlie recovery after cortical stroke, 86,88,89 is an important issue. In rats subjected to 20-minute proximal tMCAo inducing striatal SNL together with mild and inconsistent cortical SNL, Sicard et al 42 reported initial impairment but eventual full recovery in 3 weeks of subtle motor functions assessed by the adhesive test, which has been suggested to be specific to cortical lesions.…”
Section: Animal Modelsmentioning
confidence: 99%
“…These apparent discrepancies might reflect species differences but also the small degree of neuronal death in S1, the lack of co-registration between fMRI and histopathology, and the fact that fMRI was performed under general anesthesia, in the Sicard study. 42 Behavioral Correlates Although avoiding infarction of the penumbra markedly benefits behavioral outcome, 86,87 whether SNL may limit or delay functional recovery and plastic processes in the immediate periinfarct tissue, known to partly underlie recovery after cortical stroke, 86,88,89 is an important issue. In rats subjected to 20-minute proximal tMCAo inducing striatal SNL together with mild and inconsistent cortical SNL, Sicard et al 42 reported initial impairment but eventual full recovery in 3 weeks of subtle motor functions assessed by the adhesive test, which has been suggested to be specific to cortical lesions.…”
Section: Animal Modelsmentioning
confidence: 99%
“…An extreme range of reductions were observed in the left thalamus, ranging from 4% to 54%. In no region did the CBF approach the conventionally accepted ischemic threshold of 20 mL/hg min (Purves, 1972;Furlan et al, 1996;Marchal et al, 1996).…”
Section: Blood Flowmentioning
confidence: 99%
“…Cerebral ischemia causes dynamic and heterogeneous alterations of oxygen and glucose supplies and cellular metabolism [6,25]. Decreased level of glucose in ischemia is believed to play an important role in ischemic injury.…”
mentioning
confidence: 99%